ANALISIS KINERJA PETUGAS APRON MOVEMENT CONTROL (AMC) DALAM MENINGKATKAN KESELAMATAN PENERBANGAN DI BANDARA UDARA INTERNASIONAL ADI SOEMARMO SOLO - Vernanda Dwi Sasqia Putri; Suprapti Suprapti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
Apron Movement Control (AMC) is an airport personnel who has a license and rating to carry out supervision, safety of movement and crossing of the apron, ensure the cleanliness of the apron area and provide aircraft parking. Supervision carried out by Apron Movement Control (AMC) aims to create security and safety in flight activities. The purpose of this study was to determine whether the performance of AMC officers played an important role in improving flight safety at Adi Soemarmo Solo airport and what AMC officers faced in managing flight traffic to ensure safety at Adi Soemarmo Solo International airport. This research is a qualitative research using primary data and secondary data. Data collection techniques used are observation, interviews and documentation. The observation is to conduct a review or direct observation on the AMC unit. Interviews in this study were 2 AMC personnel. The documentation is by taking pictures of all events or problems in the field. The results of this study can be concluded that the performance of the AMC unit at Adi Soemarmo Airport Solo in ensuring flight safety, especially in the air side area, is very important and is said to be good because in carrying out its duties and responsibilities it is in accordance with the Standard Operating Procedure (SOP) for quality performance and instructions. specifically from Angkasa Pura. First, in terms of the allocation of parking stands for aircraft. Second, traffic control in the apron area. Third, ensure cleanliness in the air side area or apron at all times. The most common and frequent obstacle to the AMC unit at Adi Soemarmo International Airport is miss communication with the Airline or Grund Handling in terms of handling aircraft and also when minor incidents occur.